A Framework and Taxonomy for Categorizing Industrial Symbiosis in Manufacturing - Lars Jakobs; Angelika Hofer; Erwin Rauch (Журнал інженерних наук)
The industrial sector is a significant contributor to global waste, discarding vast amounts annually, which results in both environmental pollution and economic losses. A promising solution is industrial symbiosis (IS), where companies (often from different industries) identify synergies and engage in the exchange of materials, energy, water, and by-products, aiming to close the loop and enhance resource efficiency. Despite growing interest and numerous examples, comprehensive taxonomies for categorizing IS practices in manufacturing remain scarce, as existing studies often focus on individual case studies. This study addresses this gap by proposing a new general taxonomy for the manufacturing sector. Relevant studies were analyzed and synthesized through a systematic literature review of 61 studies, with 22 selected for in-depth analysis of existing IS taxonomies. The findings were refined and validated through iterative expert input, resulting in a three-level taxonomy comprising 4 primary categories, 26 secondary categories, and 119 tertiary categories. The proposed classification provides a holistic framework tailored to the manufacturing sector, enabling practitioners and researchers to gain deeper insights into IS networks and develop effective IS strategies. Future research should validate these categories through empirical studies and explore their practical applications in different manufacturing settings.